Liver function tests as an indicator of adverse maternal and fetal outcomes in patients with hypertensive disorders of pregnancy - Shah, Diya; Saha, Madhuri; Uday, Rajini; U., Ashwini Nayak; Mitra, Rusa; Fatima, Mahek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypertensive disorders of pregnancy (HDP) are significant contributors to maternal and fetal morbidity and mortality worldwide, with a prevalence in Southeast Asia ranging from 5-15% of pregnancies. In India, the incidence stands at 6.9%. Early detection and management of HDP are vital for improving outcomes. Liver function tests (LFTs) provide a cost-effective tool for assessing HDP severity and predicting complications. This study aims to evaluate the effectiveness of LFTs as a prognostic tool for adverse maternal and fetal outcomes, analyze altered LFT parameters across different HDP types and associated complications, and determine cutoff values for serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvate transaminase (SGPT), and lactate dehydrogenase (LDH) in predicting HDP. Methods: This prospective study was conducted at a tertiary care referral hospital from January 2023 to January 2024. A total of 186 pregnant women diagnosed with HDP were included, excluding those with pre-existing liver disorders. LFTs were performed, and the results were analyzed using statistical package for the social sciences (SPSS) 20.0. Results: Gestational hypertension was most common (48.9%), followed by severe preeclampsia (33.9%). Elevated LFTs (SGOT, SGPT, ALP, LDH) were significantly associated with adverse outcomes, with LDH showing high sensitivity (97.6%) and specificity (82.1%) at 150 U/l for maternal complications. Conclusions: Abnormal LFTs, particularly SGOT, SGPT, and LDH, are key prognostic markers for adverse fetal and maternal outcomes in women with HDP, with LDH having the highest predictive significance. Timely intervention for cases with elevated LFTs can reduce maternal and fetal morbidity and mortality.